2021
DOI: 10.1007/s00402-021-03966-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional stability: an experimental knee joint cadaveric study on collateral ligaments tension

Abstract: IntroductionApplying proper tension to ligaments during Total-Knee-Arthroplasty surgery is fundamental for optimal implant performance: low tensions lead to joint instability, over-tensioning to pain and stiffness. "Functional stability" must then be defined and achieved. An experimental cadaveric activity was performed to measure the minimum tension required to achieve this stability. MethodsTen knee specimens were investigated; femur and tibia were clamped to a loading-frame; constant displacement rate was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Therefore, cruciate preserving TKA, such as the BCR‐TKA design, influences the biomechanics of the cruciate ligaments but not of the collateral ligaments. Innocenti et al have reported that knee stability was significantly decreased after ACL and PCL resection [7]. They concluded that the tensions required to stabilise a knee joint are lower than the ones applied nowadays via surgical tensioners [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, cruciate preserving TKA, such as the BCR‐TKA design, influences the biomechanics of the cruciate ligaments but not of the collateral ligaments. Innocenti et al have reported that knee stability was significantly decreased after ACL and PCL resection [7]. They concluded that the tensions required to stabilise a knee joint are lower than the ones applied nowadays via surgical tensioners [7].…”
Section: Discussionmentioning
confidence: 99%
“…Innocenti et al have reported that knee stability was significantly decreased after ACL and PCL resection [7]. They concluded that the tensions required to stabilise a knee joint are lower than the ones applied nowadays via surgical tensioners [7]. In addition, Lavoie et al reported that although BCR‐TKA yield similar clinical and patient‐reported outcomes five years following the intervention compared with PS‐TKA, the BCR‐TKA had more complications such as stiffness [16].…”
Section: Discussionmentioning
confidence: 99%